2019
DOI: 10.18052/www.scipress.com/ilns.73.26
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Quality Parameters and Grain Characteristics of Rice Varieties of Afghanistan

Abstract: The present study was conducted to evaluate the antioxidant activity, grain traits and quality contents in Afghanistan’s selected rice varieties. The antioxidant capacity was measured using DPPH (1,1-diphenyl-2-picrylhydrazyl) and Reducing Power methods. Grain length, grain width and grain thickness were in the range of 5.4-7.6, 1.7-3.2, and 1.5-2.2 mm respectively. Selah Zoodras, Taram Irani and Attai-1 had the longest grain length whereas Luke was associated with high width and thickness among the varieties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Antioxidant activities showed a negative correlation with the physicochemical properties of the grain. Rayee et al [33] reported that differences in antioxidant capacity might be due to genetic variation and environmental factors that contributed to the antioxidant capacity of varieties. Mrad et al [34] stated that high temperature degraded bioactive compounds and decreased antioxidant activity in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activities showed a negative correlation with the physicochemical properties of the grain. Rayee et al [33] reported that differences in antioxidant capacity might be due to genetic variation and environmental factors that contributed to the antioxidant capacity of varieties. Mrad et al [34] stated that high temperature degraded bioactive compounds and decreased antioxidant activity in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The rice grain quality contents are determined by genetic interaction and environmental conditions [6]. Based on previous studies, rice grain quality is mostly influenced by drought stress during the reproductive stage [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the finding of the current study also revealed that the grain lipid and moisture contents were significantly lower in Akitakomachi (Table 1). Rayee., et al [30] reported that physicochemical properties of rice grain varied based on genetic background and cultivation method. The grain length in NERICA-4 (6.6 mm) and IR-28 (6.6 mm) were significantly higher compared to Akitakomachi (5.1 mm).…”
Section: Table-1mentioning
confidence: 99%